Prioridades espaciais para o desenvolvimento agrícola no Cerrado - Lemes, Larissa Pereira (2016)
Agriculture is indispensable due to food production and its importance in economy. Notwithstanding, it causes fragmentation and habitat loss, threatening species conservation. Agriculture is also responsible for global warming, due to greenhouse gases release to the atmosphere. Species suitable areas will probably change due to the changing climate, and if they are not able to adapt to the new conditions, or disperse to the new suitable area, they will become extinguished. Agriculture may occupy species future suitable area or block species dispersion. Implement areas for species protection is urgent due to agriculture threats. However, conflicts between conservation and economy have been frustrating conservation spatial planning and contributing to residual protected areas. Facing conservation difficulty, I sought to identify spatial priorities for agricultural development in the Brazilian Cerrado, and also minimize mammal biodiversity loss. It is possible to use the necessary areas for crop plantations and still preserve about 70 per cent of mammals suitable area, now and in the future. Notwithstanding, species future suitable area is restricted and unbridled agricultural progress may occupy this area. It is urgent for science to guide agricultural development in the Brazilian Cerrado so the important areas for species survival still exist in the future. It is possible to conciliate conservation and economic development, and minimize conflicts.